Impacts of academic resilience, academic procrastination and self-regulation on student engagement among undergraduates in UTAR, Kampar Campus - Koghulan, Agilanananth; Low, Xiao Ying; Ng, Huat Lin; Ng, Shi Qin (2024)
Student engagement is important for students at all levels. It is important for students to maintain a high level of engagement in their studies to reach their goals, have higher achievement and a sense of fulfilment. The purpose of this research is to find out the influence of academic resilience, academic procrastination and self-regulation on student engagement among undergraduates in UTAR, Kampar campus. This research will help undergraduates and readers to have more understanding about the factors that influence student engagement. Quantitative research was used for this research by using online questionnaires as the data collection method. Cross-sectional design was used as the research design for this research. A total of 367 undergraduates from Universiti Tunku Abdul Rahman, Kampar campus participated in the survey. The result has shown that academic resilience, academic procrastination, and self-regulation are significantly correlated to student engagement. Academic resilience and self-regulation are positively related to student engagement and academic procrastination is negatively related to student engagement